PENGARUH PEMBERIAN TEPUNG KEONG SAWAH (Pila ampulacea) SEBAGAI PENGANTI TEPUNG IKAN DALAM PAKAN TERHADAP KUALITAS TELUR BURUNG PUYUH (Coturnix coturnix Japonica) - Rondonuwu, Crisye R.; Saerang, J.L.P.; Utiah, W.; Regar, M.N. (Universitas Sam Ratulangi, 2018)
SUBSTITUTION EFFECT OF FISH MEAL WITH SNAIL MEAL (Pila ampulacea) IN RATION Â ON QUILL EGG QUALITY (Coturnix coturnix Japonica). The objective of this study was to evaluate the substitution effect of fish meal with snail meal in ration on quill egg quality. Total of 60 quills at age of 5 weeks old were used on the period study of 8 weeks. The completely randomized design was applied in this study consisted of 4 treatments with 5 replications at each treatment. The treatments were levels of snail meal substituting fish meal in ration as follows: R0 = 0% snail meal + 15 % fish meal, R1 = 5% snail meal + 10% fish meal, R2 = 10% snail meal + 5% fish meal, R3 = 15% snail meal + 0% fish meal. Variables measured in this study were including egg weight, yolk index, albumin index, yolk color and shell thickness. Results showed that snail meal affected significantly (P<0.05) the egg weight and albumin index, did not affect yolk index, yolk color and shell thickness. Therefore, it can be concluded that substitution of fish meal with snail meal up to 15% in ration of quill produced good products of egg weight, yolk index, albumin index, yolk color and shell thickness.Key words: Snail meal, fish meal, quill egg quality.